Abuse Of Volatile Solvents And Inhalants: Papers Presented At A W.H.O Advisory Meeting - Grant, M.; Arif, A.E.; Navaratnam, V. (Pusat Penyelidikan Dadah Kebangsaan, Universiti Sains Malaysia, 1988)
Most regions of the world have shown concern about solvent substance inhalation as a form of drug abuse. This concern has been expressed in the past at various international meetings, including the Executive Board of the World Health Organization and the World Health Assembly and the United Nations Commission on Narcotic Drugs.